Sharing the moment's discourse: Virginia Woolf, D. H. Lawrence and Albert Einstein in the early twentieth century - Crossland, R (2010)
Using Gillian Beer's suggestion that literature and science 'share the moment's discourse' (Open Fields, 1996), this thesis explores the ideas associated with Albert Einstein's three revolutionary 1905 papers, examining the ways in which similar concepts appeared across disciplines during the early part of the twentieth century, and focusing in particular on their manifestation within the literary works of Virginia Woolf and D. H. Lawrence. The study seeks to distinguish between instances of direct influence and a shared contemporary discourse, arguing that the analysis of both is essential to studies within the field of literature and science. Part I focuses on concepts of duality and complementarity, considering Max Planck's introduction of the quantum, Einstein's development of light quanta, Louis de Broglie's wave-particle duality and Niels Bohr's principle of complementarity. It analyses other contemporary discussions of duality and complementarity, and explores Virginia Woolf's attempts to simultaneously express both sides of dualistic models, suggesting that Woolf is a complementary writer. Part II focuses on Einstein's theories of relativity, exploring D. H. Lawrence's adoption thereof in Fantasia of the Unconscious (1922), in particular his claim that 'we are in sad need of a theory of human relativity'. It argues that this proposed theory is directly relevant to Lawrence's fictional works, both those that precede Fantasia and those that follow it. It also analyses the impact on Lawrence of contemporary ideas of relativism, especially those of William James as expressed in Pragmatism (1907). Part III explores the ways in which both Woolf and Lawrence write about individuals within crowds. It considers the possible links between such scenes and Einstein's paper on Brownian motion as well as contemporary studies of crowd psychology. It suggests that individual characters within modernist works can be considered as similar to the individual particles suspended in a mass which exhibit Brownian motion.